Investigation Of Parameters Affecting Rotary Engine By Means Of A One Zone Thermodynamic Model - Kutlar, Osman Akin; Cihan, Omer (Aperta, 2022)
The scope of this work was to establish a one-zone thermodynamic calculation model to analyze 13B multi-side port rotary engine on the base of Mazda RX-8. Volume variation was calculated according to the basic geometrical data of the engine and heat transfer was calculated using Wilmer's heat transfer coefficient. Combustion process was defined as heat addition according to Vibe function and simultaneously converting fresh charge to combustion products. To account related losses, discharge drag, leakage, crevice volumes, and mean friction pressure were taken into account. The port fuel injection (homogeneous mixture) was used in the model assumptions. Model calculations were validated with experimental data. Many parameters were investigated in the model such as combustion chamber pressure, mass and engine torque at different speeds, and full load conditions. Moreover, the effect of the Vibe parameter, combustion duration, and intake port variations on the torque was investigated. The highest torque value was observed in the model with only primary intake port at low rpm (1000-3750 rpm) and primary and secondary port at mid rpm (3750-6250 rpm). Higher torque values were obtained from two secondary and two auxiliaries than primary, secondary, and auxiliary in the literature at high rpm (6250-8500 rpm). Combustion duration, Vibe parameter, and variations of different intake ports have a significant effect on the engine characteristics. The thermodynamic model developed in this study may be used as an effective tool to examine the performance parameters of the Wankel engine.